Dydaktyka technologiczna i ukryty program kształcenia na łamach czasopism „Polonistyka” i „Matematyka” z lat 1945–1961 - Jasiński, Krzysztof; Kopacz, Agnieszka (Biuletyn Historii Wychowania, 2023)
The text presents an analysis of two magazines: “Polish Studies” and “Mathematics”, from the point of view of technological teaching and hidden concealed curriculum of the authorities of the Polish People’s Republic in 1945–1956. As previous studies indicate, the assumptions of both concepts are consistent with the educational policy in that time but an analysis of the specific titles in this regard has been rarely carried out. The article consists of a theoretical part with a definition of the concepts necessary to understand the topic, and outlines the historical context. It is followed by a research part presenting the methodology of the research and a description of selected texts. They open the way for the development of subsequent annuals and a systematic comparative analysis.